On Western Terrorism : From Hiroshima to Drone Warfare - Chomsky, Noam and Vltchek, Andre (London Pluto Press, 2013)
Noam Chomsky, the dissident intellectual, discusses Western power and propaganda with filmmaker and investigative journalist Andre Vltchek. The discussion weaves together a historical narrative with the two men's personal experiences which led them to a life of activism. The discussion includes personal memories, such as the New York newsstand where Chomsky began his political education, and broadens out to look at the shifting forms of imperial control and the Western propaganda apparatus. Along the way the discussion touches on many countries of which the authors have personal experience, from Nicaragua and Cuba, to China, Chile, Turkey and many more
Include Colour Illustration and ndex
Keywords: Terrorism -- Western countries -- Diplomatic relations -- World politics